Nitrate adsorption in variable charged soils - Alcântara, Marco Aurélio Kondracki de; Camargo, Otávio Antonio de (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to assess the adsorptive behavior of nitrate due to net charge (pH) modifications caused by the addition of acids, bases (carbonates), phosphate and sulfate. Samples of A and B horizons of two soils: an Ustox and an Ustalf . Freundlich isotherms were adjusted in order to verify the influence of the different treatments. The Freundlich model fits well to experimental data. There is significance correlation between pH and net charge for the soils, considering the treatments applied to the B horizon of the Ustox soil. Nitrate adsorption in the A and B horizons is different for the two soils. In Ustox soil, adsorption is greater in subsuperficial than in superficial horizon. In Ustalf soil, adsorption is greater in the superficial horizon than in the subsuperficial one. Sulfate and phosphate additions result in little reduction on the nitrate adsorption comparing to the Ustox B horizon.